The Effect of the Arctic Oscillation on the Predictability of Mid-High Latitude Circulation in December - Zheng, Zhihai; Ban, Jin; Li, Yongsheng (Frontiers in Physics, 2021)
The impact of the Arctic Oscillation (AO) on the predictability of mid-high latitude circulation in December is analysed using a full set of hindcasts generated form the Beijing Climate Center Atmospheric General Circulation Model version 2.2 (BCC_AGCM2.2). The results showed that there is a relationship between the predictability of the model on the Eurasian mid-high latitude circulation and the phase of AO, with the highest predictability in negative AO phase and lowest predictability in normal AO phase. Moreover, the difference of predictability exists at different lead time. The potential sources of the high predictability in the negative AO phase in the BCC_AGCM2.2 model are further diagnosed. It is found that the differences of predictability on the Eurasian mid-high latitude circulation also exist in different Arctic sea ice anomalies, and the model performs well in reproducing the response of Arctic sea ice on the AO. The predictability is higher when sudden stratospheric warming (SSW) events occur, and strong SSW event tend to form a negative AO phase distribution in the Eurasian mid-high latitudes both in observation and model. In additional, the model capture well the blocking over the mid-high latitudes, it may be related to the relatively long duration of the blocking. Changes in the AO will affect the blocking circulations over the mid-high latitudes, which partly explains the high predictability of the model in negative AO phases from the aspect of the internal atmospheric dynamics.